Penerapan Range of Mation (ROM) terhadap Peningkatan Kekuatan Otot dengan Kasus Stroke Non Hemoragik pada Ny. A Di UPT PSTW Jember - Museva, Anis; Khotimah, Husnul; hafifah, Vivin (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Background: Stroke remains a major health issue both in Indonesia and globally. Non-hemorrhagic stroke is a leading cause of physical disability, resulting in decreased muscle strength and motor function. Physical rehabilitation, including Range of Motion (ROM) exercises, plays a crucial role in the recovery of stroke patients by restoring muscle function and improving muscle strength. Objective: This study aims to evaluate the effectiveness of ROM exercises in improving muscle strength in non-hemorrhagic stroke patients with physical mobility impairment. Methods: A descriptive study with a case study approach was conducted on one non-hemorrhagic stroke patient who was given passive ROM exercises for 7 days, with a frequency of twice a day (morning and evening). The instruments used included Standard Operating Procedures (SOP) and a Manual Muscle Testing (MMT) observation sheet to assess muscle strength before and after the passive ROM intervention. Results: The study showed a significant increase in muscle strength after ROM exercises. Muscle strength consistently improved throughout the intervention, indicating that ROM exercises are effective in enhancing muscle strength in non-hemorrhagic stroke patients. Conclusion: Regular ROM exercises can increase muscle strength in non-hemorrhagic stroke patients. Initially, the patient's left extremity muscle strength was at a scale of 3, and after 7 days of ROM exercises, it improved to a scale of 4. This study provides evidence that ROM exercises are effective for stroke patients